The level of parents’ awareness of the importance of kindergarten in Hafar Al-Batin Governorate - Al-Harbi, Rawan Ali (Journal of Educational and Psychological Sciences, 2023)
The current study aimed at knowledge and awareness of parents of the importance of kindergartens in the province of Harf Al-Batin and the researcher used the descriptive method and relied on the questionnaire in the collection of information and applied to a sample of (622) parents distributed randomly according to variables (type/educational level) and the results indicated that there are statistically significant differences when parents are aware of the importance of kindergartens in the governorate of Harf Al-Batin With a significant ratio (0.00) at the level of significance (0.05) for mothers with an average (2.90) as shown by statistically significant differences in the awareness of educated and uneducated parents, which are attributable (to the educational level) as shown by differences Towards graduate studies with an average (1.89), while secondary and below came in second place with an average (1.60), while bachelor’s degree is in third place with an average (1.49) and in diploma in last place with an average (1.03).